2014
DOI: 10.1155/2014/627041
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is Associated with Reduced Leptin and Neuropeptide Y Levels and Higher Pain Experience in Patients with Fibromyalgia

Abstract: Smoking deregulates neuroendocrine responses to pain supporting production of neuropeptide Y (NpY) by direct stimulation of nicotinic receptors or by inhibiting adipokine leptin. Present study addressed the effect of cigarette smoking on adipokines and pain parameters, in 62 women with fibromyalgia (FM) pain syndrome with unknown etiology. Pain was characterized by a visual analogue scale, tender point (TP) counts, pressure pain threshold, and neuroendocrine markers NpY and substance P (sP). Levels of IGF-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…NPY is a potent stimulator of feeding and principally produced in the arcuate nucleus of the hypothalamus. NPY production is suppressed by cigarette smoke exposure (SE) as well as postsynaptic NPY Y1 receptor levels leading to anorexia and weight loss [11,24]; whereas smoking cessation was shown to increase NPY production resulting in overeating and weight gain [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…NPY is a potent stimulator of feeding and principally produced in the arcuate nucleus of the hypothalamus. NPY production is suppressed by cigarette smoke exposure (SE) as well as postsynaptic NPY Y1 receptor levels leading to anorexia and weight loss [11,24]; whereas smoking cessation was shown to increase NPY production resulting in overeating and weight gain [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed in the introduction, leptin appears to be critical in the development of allodynia and it may contribute to the development of neuropathic pain (Maeda et al, 2009). Some have suggested that a decoupling of leptin and neuropeptide Y signaling may account for the higher pain report in smokers with fibromyalgia (Bokarewa, Erlandsson, Bjersing, Dehlin, & Mannerkorpi, 2014). Again the lack of human studies requires that existing animal literature guide the interpretation of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more interestingly, as the pain level (as judged by two different pain score systems) increased, the concentration of NPY showed concomitant increase [141]. A study by Bokarewa et al [142] evaluated the role of tobacco (cigarette smoking) in women with fibromyalgia. Interestingly, the women who smoked reported significantly higher levels of pain [142].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…A study by Bokarewa et al [142] evaluated the role of tobacco (cigarette smoking) in women with fibromyalgia. Interestingly, the women who smoked reported significantly higher levels of pain [142]. At the same time, these women who smoked were found to have altered levels of leptin and NPY [142].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 1 more Smart Citation